DEVELOPMENT OF BUSINESS LAW IN THE PERSPECTIVE OF PANCASILA IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - I Made Gunartha; Dewa Gede Pradnyana Yustiawan (Transpublika Publisher, 2023)
This article aims to explore the development of business law in the context of Pancasila during the era of the Industrial Revolution 4.0. The research methodology used is normative juridical, which examines the implementation of positive legal provisions in business law. The data used includes primary and secondary sources, obtained from legal products related to business and trade. The rapid globalization brought by the 21st century industrial revolution has resulted in significant changes in various aspects of law, politics, economics, technology, and culture. As the Industrial Revolution 4.0 relies heavily on telematics (telecommunications, media, and information), it is essential to adjust regulations in the field of business law to accommodate these changes. The Indonesian government must engage in legal development, legal harmonization, and legal reconstruction to update legal products in line with the global situation. This includes building a legal system that reflects Pancasila and the 1945 Constitution to adapt to the industrial era 4.0. As the development of business law in the Industrial 4.0 era must be consistent with Pancasila's values and the 1945 Constitution, it is crucial to prioritize these values in legal development.